COP, Gender Quotas, and Policies: Implications for the MENA Region and Beyond - Najjar, Dina; Mohammed, Kamaldeen (Wilson center, 2024)
Recently, we reflected on the outcomes of the 28th Conference of Parties (COP) meetings for gender policy. The annual COP represents the decision-making arm of the United Nations Framework Convention on Climate Change (UNFCCC), whose core mandate is to review and assess the measures taken by parties and progress made in achieving stabilization of greenhouse gas emissions globally. The most recent COP, held in Dubai, UAE, was the largest gathering so far, with about 85,000 participants in total, including more than 150 heads of state and governments.